OPTIMIZING PREGRAVID PREPARATION: A MULTI-MODAL CLINICAL STRATEGY FOR MITIGATING GESTATIONAL COMPLICATIONS AND CONGENITAL FETAL ABNORMALITIES (Multidisciplinary Journal of Science and Technology, 2026)
To evaluate the efficacy of an optimized, evidence-based pregravid preparation bundle in preventing adverse maternal and neonatal outcomes.